Small is bright and big is dark in synaesthesia. - Cohen Kadosh, R; Henik, A; Walsh, V (2007)
In synaesthesia, certain perceptual or conceptual stimuli (called inducers), trigger an additional concurrent experience. For example, I.S., a digit-colour synaesthete, experiences the colour green whenever he sees the digit 7. Since Galton's seminal report on synaesthesia [1], it has been a commonly held view that digit-colour synaesthesia is highly idiosyncratic: that is, the same inducer, for example, the digit 7, will evoke different experiences in different synaesthetes. Moreover, the assumption that inducer-concurrent relationships are random is rarely questioned [2] and is based mainly on comparing the salient components of the inducer and the resulting synaesthetic perception. In the case of digit-colour synaesthesia, for example, the name of the colour is compared with the name of the digit. Little or no attention has been paid to other components of the colour or digit, such as luminance, saturation, ordinality or cardinality, which are neither explicit nor cognitively penetrable to the synaesthete. Here we report evidence of a systematic organisation relating luminance and number magnitude in digit-colour synaesthesia. We found that this organisation is based on cardinality rather than ordinality and follows the Weber-Fechner law, which has been reported previously for numerical representation in humans and monkeys [3]. Our results challenge the underlying assumptions about the mechanisms underlying synaesthesia and its developmental trajectories, and the link between luminance level and numerical magnitude strongly supports the idea of a shared magnitude representation [4]. © 2007 Elsevier Ltd. All rights reserved.